المهن الإقتصادية في الجزائر خلال العهد العثماني - خضراوي جناة (My University, 2025)
Summary The topic addresses economic professions In Algeria during the Ottoman era, focusing on the economic aspects that characterized this period. Algeria witnessed a variety of professions across different sectors of the economy. In agriculture, professions such as farming, livestock herding, and fishing were prominent. In the industrial sector, craftspeople, sculptors, dyers, and tailors played significant roles. In the commercial domain, port workers such as officers and port commanders were known, along with market supervisors, trade trustees, and vendors. Together, these professions contributed to supporting and strengthening the Algerian economy during the Ottoman period, reflecting the vitality and diversity of economic activity at the time. Ultimately, their working conditions varied, and each profession had Its own specialized methods and tools. ------------------------- الملخص بالعربية: يتناول الموضوع المهن الاقتصادية في الجزائر خلال العهد العثماني، مركّزًا على الجوانب الاقتصادية التي ميّزت هذه الفترة. فقد شهدت الجزائر تعدد المهن في مختلف فروع المجال الاقتصادي؛ فمن الجانب الزراعي، برزت مهنة الفلّاح، ومربي المواشي، والصيادين، أما في الجانب الصناعي، فقد ظهرت مهن الحرفيين، والنحّاتين، والصبّاغين، والخياطين. وفي الجانب التجاري، عُرفت مهن عمال الموانئ مثل الضابط، وقائد المرسى، إلى جانب قائد الأسواق، وأمين التجار، والبائعين. وقد ساهمت هذه المهن مجتمعة في دعم وتقوية الاقتصاد الجزائري خلال العهد العثماني، ما يعكس حيوية النشاط الاقتصادي وتنوعه آنذاك. وفي الأخير، اختلفت ظروفهم المهنية، وتعددت وسائل عملهم في كل مهنة اختصوا فيها. ----------------------------------------------  Résumé en français. . : Le sujet traite des professions économiques en Algérie durant la période ottomane, en mettant l’accent sur les aspects économiques caractéristiques de cette époque. L’Algérie a connu une diversité de métiers dans différents domaines économiques. Dans le secteur agricole, on retrouve les métiers de cultivateur, d’éleveur et de pêcheur. Dans le secteur industriel, les artisans, sculpteurs, teinturiers et tailleurs étaient présents. Quant au secteur commercial, il comprenait des métiers liés aux ports comme les officiers, les chefs du port, ainsi que les responsables des marchés, les intendants des commerçants et les vendeurs. Ces métiers ont tous contribué au renforcement et au soutien de l’économie algérienne durant l’époque ottomane, reflétant ainsi la vitalité et la diversité de l’activité économique à cette période. Enfin, les conditions professionnelles différaient d’un métier à l’autre, de même que les moyens de travail propres à chaque spécialité
Keywords: المهن الاقتصادية، العهد العثماني، الفلاحة والرعي، الحرف والصناعات، التجارة والموانئ